Abstract ID: 248 A validated MC model of the University of Birmingham MC40 medical beam line. (October 2017) - Price, Tony; Parker, David; Manolopolous, Spyros; Green, Stuart
Abstract : The University of Birmingham MC40 Cyclotron is capable of delivering up to 40 MeV protons and 53 MeV He ions at a huge range of currents varying from fA to μ A. A switching magnet allows the beam to be transported to one of twelve experimental areas. One of these is the medical beam line, which, in recent years has been used for the development of a novel proton CT device, radiobiological experiments, and proton range verification. We will present a validated MC model (using Geant4.10) of the medical beam line, demonstrating the excellent agreement between energy measurements and simulations, beam divergences, and scattering profiles through various materials. These three points are essential for all experiments conducted on the beam line. If time permits, we will also highlight some of the improvements made to the beam line where simulations formed an essential part of the design work such as a beam flattering system.